Design of the modified oxide-nickel electrode with improved electrical characteristics - Sincheskul, Alexander; Pancheva, Hanna; Loboichenko, Valentyna; Avina, Svetlana; Khrystych, Olena; Pilipenko, Alexei (Eastern-European Journal of Enterprise Technologies, 2017)
The influence of lithium hydroxide was examined on the characteristic features of charge and discharge and electrical parameters of the sintered oxide-nickel electrode in a solution of potassium hydroxide. It is shown that the introduction of LiON to the composition of electrolyte does not lead to a change in the specificity of charge and discharge processes of the electrode. The experimental work conducted allowed us to establish dependences that connect the magnitude of analytical concentration of the Li+ ions to specific capacity and capacity output of the electrode. The results obtained show that an increase in the content of Li+ ions in the electrolyte from 1 to 100 g·l–1 causes a growth of the electrode’s specific capacity from 0.79 (А·h)·cm–2 to 1.84 (А·h)·cm–2. It is optimal to introduce LiOH to the electrolyte in the amount of 30‒50 g·l–1. It was established that the magnitude of specific capacity of the oxide-nickel electrode depends on the number of charge-discharge cycles and increases with an increase in the number, which is related to the slow character of the course of mass transfer processes in the volume of active mass of the electrode.